Setting of import tolerances for hexythiazox in blackberries and raspberries - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Gowan Crop Protection Limited submitted a request to the competent national authority in Finland to set an import tolerance for the active substance hexythiazox in blackberries and raspberries. The data submitted in support of the request were found to be sufficient to derive maximum residue level (MRL) proposals of 3 mg/kg for raspberries and blackberries. Adequate analytical methods for enforcement are available to control the residues of hexythiazox in the plant matrices under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the intake of residues resulting from the use of hexythiazox according to the reported agricultural practices is unlikely to present a risk to consumer health.